Dysfunctional platelet membrane receptors: from humans to mice - Ware, Jerry (Thrombosis and Haemostasis, 2004)
Insights into hemostasis and thrombosis have historically benefited from the astute diagnosis of human bleeding and thrombotic disorders followed by decades of careful biochemical characterization. This work has set the stage for the development of a number of mouse models of hemostasis and thrombosis generated by gene targeting strategies in the mouse genome. The utility of these models is the in depth analysis that can be performed on the precise molecular interactions that support hemostasis and thrombosis along with efficacy testing of various therapeutic strategies. Already the mouse has proven to be an excellent model of the processes that support hemostasis and thrombosis in the human vasculature. A brief summary of the salient phenotypes from knockout mice missing key platelet receptors is presented, including the glycoprotein (GP) Ib-IX-V and GP IIb/IIIa (αIIb/β3) receptors; the collagen receptors, GP VI and α2/β1; the protease activated receptors (PARs); and the purinergic receptors, P2Y1 and P2Y12. A few differences exist between mouse and human platelets and where appropriate those will be highlighted in this review. Concluding remarks focus on the importance of understanding the power and limitations of various in vitro, ex vivo and in vivo models currently being used and the impact of the mouse strain on the described platelet phenotype.
Keywords: Animals; bleeding time; comparative study; disease models; animal; mice; mice knockout; mice mutant strains; tail/blood supply; platelets